ECONOMIC JUSTICE AND THE SPIRIT OF ISLAMIC ECONOMICS: A REVIEW OF JOSEPH E. STIGLITZ AND MUHAMMAD YUNUS’ THOUGHTS ON ECONOMIC AND LAW - Muslimin, JM.; Romlah, Siti; Ramadhan, Suci (Jurnal Syarikah : Jurnal Ekonomi Islam, 2022)
This paper aims to analyze the political discourse of economic law in the era of globalization in developing countries from the perspective of Joseph E. Stiglitz and Muhammad Yunus. The globalization has affected various sectors of people’s lives, including the pattern of free markets that occur for all lower-middle-income countries, instead destroys them. Many economists who pay attention to this issue, include Joseph E. Stiglitz and Muhammad Yunus who have greatly influenced the global world regarding economic development. This qualitative research uses a comparative approach, and secondary data such as journal articles, books, and reports. Data were collected through documentation techniques and analyzed using interactive model analysis. The result indicates that the discourses of thought between Joseph E. Stiglitz and Muhammad Yunus about the politics of economic law have similarities and differences. The two economists agree that economics, law, and humanity have a very close connection. They recommended that efforts to reform mondial policies be carried out based on participation, equality, independence, justice and democracy. In addition, the effects of globalization in the economic sector need to be regulated fairly. Thus, their thoughts are in line to the basic principles of Islamic economics: principles of equilibrium and justice.